2019
DOI: 10.1177/2325967119838249
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Outcomes After Arthroscopic Lamina-Specific Double-Row Repair of Large Delaminated Rotator Cuff Tears in Active Patients

Abstract: Background: The presence of delamination and a larger rotator cuff tear (RCT) size have been associated with poorer outcomes in rotator cuff repair. Therefore, we developed a new surgical procedure, arthroscopic lamina-specific double-row fixation (ALSDR), for the repair of large delaminated RCTs. Purpose: To investigate the clinical outcomes, magnetic resonance imaging findings, and satisfaction with several variables after ALSDR for large delaminated RCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Comparisons between patients with intact and retorn tendons in the active group suggested that shoulder activity had a generally negative effect on shoulder function in patients with retears, supporting the conclusions of previous studies. 23,33,34 Notably, patients with retears and high VAS scores for pain were only observed in the active group, indicating that the pain is probably enhanced by shoulder activities. The above findings of this study helped reconcile the contradicting results of previous studies 9,19,20,32,38 on the relationship between shoulder function and retears, as the activity levels of the patients in these investigations, although not clearly reported, could have been different.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Comparisons between patients with intact and retorn tendons in the active group suggested that shoulder activity had a generally negative effect on shoulder function in patients with retears, supporting the conclusions of previous studies. 23,33,34 Notably, patients with retears and high VAS scores for pain were only observed in the active group, indicating that the pain is probably enhanced by shoulder activities. The above findings of this study helped reconcile the contradicting results of previous studies 9,19,20,32,38 on the relationship between shoulder function and retears, as the activity levels of the patients in these investigations, although not clearly reported, could have been different.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, this method has been used by other investigators and has been shown to be reliable. 33,34 Second, the number of retears was small, which might weaken the statistical power of related analyses. However, this was mainly the result of the low retear rate of the sedentary group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthroscopic rotator cuff repair using suture-bridge technique can achieve good to excellent clinical results. The shoulder functional outcomes were signi cantly improved even in the absence of RC healing [1,18]. The patient satisfaction rate was above 80% after the surgery.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, the resulting area calculation assumes a square, 2-dimensional tear shape, while shape variations in individual tear defect configurations exist. Still, the authors felt that the arthroscopically determined square centimeter measurements of tear size were an improvement over other methods, such as nonquantitative, unidirectional, or solely derived from magnetic resonance imaging, to describe rotator cuff tear size 25 , 26 , 27 and allowed the authors to reproducibly define both the initial and residual rotator cuff tear defects that were present. Also, the arthroscopic measurements were taken to an accuracy of 1 cm, thus introducing a “rounding error” that contributes to inaccuracy within the tear area calculation.…”
Section: Discussionmentioning
confidence: 99%